Enriching oil palm genetic resource in India - Murugesan, P; Kumar, K Sunil; Mathur, R K (Indian Horticulture, 2019)
The seeds of the germplasm were brought to regional station of Indian Institute of Oil Palm Research Palode and germinated seeds were raised in the quarantine facility established for imported germplasm. Nigerian and Angolan resources could be explored for future collection/exchange from Malaysian Palm Oil Board. In view of narrow of resources in the country collaborative research projects need to be taken up with the help of international organizations for exchange from West Africa for trait specific germplasm. The present germplasm supplied by Malaysia would be highly useful to India in widening our genetic base and thus help us in strengthening crop improvement programmes.